Bifurcated urban integration: The selective dis- and re-assembly of infrastructures. (August 2019) - Macrorie, Rachel; Marvin, Simon
Urban integration (UI) has emerged as the guiding maxim for enabling efficient resource flows and smart and connected cites. The last decade has led to renewed interest in exploiting interconnections to optimise city capacities in urban policy, practice and research. However, the imperative for integration across resources, infrastructures, sectors and disciplines remains largely unquestioned, and its socio-political and environmental implications receive little critical attention. This paper subjects the ideas and practices of UI to scrutiny. We argue that integration-in-practice (as opposed to integration-in-theory) is partial and selective in its objects of combination and outcomes. The key issue this raises is whether the promise of new metropolitan-wide imaginaries of horizontal integration gives way to more selective logics of vertical integration that privilege socially and spatially valued enclaves. Rather than challenge urban splintering, UI practices would therefore reinforce urban infrastructure divides. The paper argues that a subtle shift is taking place in the UI discourse that whilst promising resource sustainability and metropolitan inclusivity, re-prioritises and re-intensifies more selective infrastructural planning processes. We term this new emerging mode bifurcated urban integration (BUI).